2017
DOI: 10.1186/s12887-017-0946-1
|View full text |Cite
|
Sign up to set email alerts
|

Health, nutrition, and development of children born preterm and low birth weight in rural Rwanda: a cross-sectional study

Abstract: BackgroundAs care for preterm and low birth weight (LBW) infants improves in resource-limited settings, more infants are surviving the neonatal period. Preterm and (LBW) infants are at high-risk of nutritional and medical comorbidities, yet little is known about their developmental outcomes in low-income countries. This study evaluated the health, nutritional, and developmental status of preterm/LBW children at ages 1–3 years in Rwanda.MethodsCross-sectional study of preterm/LBW infants discharged between Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 35 publications
2
34
3
3
Order By: Relevance
“…As expected, there was higher burden of stunting, underweight, and wasting (58.8%, 47.5%, 25.8%, respectively) among children enrolled in the PDC aged 6-59 months between 2014 and 2017, compared to the national prevalence of undernutrition among children under five years of age in rural Rwanda (stunting: 40.6%, underweight: 10.0% and wasting: 2.3%) [8]. Two earlier studies in Rwanda and Burundi showed elevated rates of stunting, underweight and wasting among preterm and LBW infants, however stunting in our sample was lower (58.8% in PDC versus 79.0% in Rwanda without PDC at ages 12-36 months and 81.0% in Burundi at age 2 years) and prevalence of wasting was higher (25.8% PDC versus 9.0% and 18.0%, respectively) [9,22]. It is important to note that both of these studies had a large number of children that could not be located for assessment (23-46%) or died (4-6%) indicating potential Table 1: Associations between selected demographic and clinical characteristics of Pediatric Development Clinic (PDC) participants and their families with malnutrition outcomes;…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…As expected, there was higher burden of stunting, underweight, and wasting (58.8%, 47.5%, 25.8%, respectively) among children enrolled in the PDC aged 6-59 months between 2014 and 2017, compared to the national prevalence of undernutrition among children under five years of age in rural Rwanda (stunting: 40.6%, underweight: 10.0% and wasting: 2.3%) [8]. Two earlier studies in Rwanda and Burundi showed elevated rates of stunting, underweight and wasting among preterm and LBW infants, however stunting in our sample was lower (58.8% in PDC versus 79.0% in Rwanda without PDC at ages 12-36 months and 81.0% in Burundi at age 2 years) and prevalence of wasting was higher (25.8% PDC versus 9.0% and 18.0%, respectively) [9,22]. It is important to note that both of these studies had a large number of children that could not be located for assessment (23-46%) or died (4-6%) indicating potential Table 1: Associations between selected demographic and clinical characteristics of Pediatric Development Clinic (PDC) participants and their families with malnutrition outcomes;…”
Section: Discussioncontrasting
confidence: 74%
“…In Rwanda, childhood malnutrition is a significant problem-with 41% of children under five years stunted, 10% underweight and 2% wasted in rural areas [8]. While the burden of malnutrition in children with increased biologic or social vulnerability has not been fully documented in Rwanda, 78% of premature and/or LBW children discharged from a rural hospital neonatal unit were stunted and 9% wasted at ages 1-3 years [9].…”
Section: Introductionmentioning
confidence: 99%
“…Akibat komorbiditas ini dan kondisi dasar bayi prematur, klinisi cenderung menunda pemberian susu sehingga terjadi EUGR. 14,15 Perubahan pedoman nutrisi untuk bayi prematur tahun 2018…”
Section: Malnutrisi Pada Bayi Prematurunclassified
“…Akibat komorbiditas ini dan kondisi dasar bayi prematur, klinisi cenderung menunda pemberian susu sehingga terjadi EUGR. 14,15…”
Section: Tata Laksana Nutrisi Untuk Bayi Prematur Selama Perawatan Niunclassified